2011
DOI: 10.5539/jas.v4n1p104
|View full text |Cite
|
Sign up to set email alerts
|

Novel BsuRI-c.930A>G-FSHb Associated with Litter Size Traits on Large White X Landrace Crossbred Sows

Abstract: The objective of this experiment was to identify the novel single nucleotide polymorphisms (SNPs) on porcine follicle stimulating hormone  subunit (FSH) genes. Moreover, their association with litter size traits in commercial pigs will be analyzed. 1,155 Large White x Landrace crossbred sows were bled and DNA was extracted. The records included total number of piglet born (TNB), number of piglet born alive (NBA), number of piglets stillbirth (SB) and number of piglets mummified (MM). The known sequence of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…FSHβ (c.930A>G) SNP: The length of amplified PCR product (930 bp) was similar to the findings of Pripwai and Mekchay (2011). Monomorphism at this SNP locus was however contrary to the findings of Pripwai and Mekchay (2011) in crossbred pigs of Large White and Landrace breeds. They reported that frequency of A and G allele at FSHâ (c.930A>G) SNP locus was 0.81 and 0.19, respectively.…”
Section: Esr1 (C1227c > T) Snpsupporting
confidence: 64%
See 1 more Smart Citation
“…FSHβ (c.930A>G) SNP: The length of amplified PCR product (930 bp) was similar to the findings of Pripwai and Mekchay (2011). Monomorphism at this SNP locus was however contrary to the findings of Pripwai and Mekchay (2011) in crossbred pigs of Large White and Landrace breeds. They reported that frequency of A and G allele at FSHâ (c.930A>G) SNP locus was 0.81 and 0.19, respectively.…”
Section: Esr1 (C1227c > T) Snpsupporting
confidence: 64%
“…Niu et al (2006) studied the polymorphism of Prei3 (T802G) in seven pig breeds and suggested that pre-implantation protein 3 (prei3) is one of the promising candidate gene for litter size in pigs. Pripwai and Mekchay (2011) identified a novel SNP at BsuRIc 930A>G in porcine follicle stimulating hormone (FSHâ) gene having significant association with litter size in commercial pigs. Kumchoo and Mekchay (2015) identified SNP at c.425G>A in OPN gene having significant association with litter size in commercial Thai Large White pigs.…”
mentioning
confidence: 99%